Evaluation of Personal-Social Developmental Skills Levels in Children with Early Treated Phenylketonuria - Zahra Ghadbeigi; Firouzeh Sajedi; Akbar Biglariyan; Gita Movallali; Sepideh Nazi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: This Study aimed to investigate the level of personal-social developmental skills in 1-4 years old children with early treated phenylketonuria. Materials & Methods: This analytic, cross-sectional study has been done on 40 children 1-4 years old referred to clinics of phenylketonuria (PKU) who were diagnosed through screening at birth and were treated. The measurements were a demographic questionnaire, ASQ (Ages & Stages Questionnaire) and clinical assessment by pediatrician. Forty children were also selected randomly as control group from kindergartens of Tehran and completed the questionnaires. Data were analyzed by SPSS 19.0 software. Results: The mean age of Children was 30.7 (±10.5) months in the control group and 27.7 (±11.0) months in the case groups. There was no significant differences between two groups in terms of delivery type and the current and birth height, weight and head circumference. There was a significant difference between two groups regarding personal-social developmental skills (P<0.001). Conclusion: The level of personal-social developmental skills in the children with early treated Phenylketonuria is lower than normal children. Early diagnosis and intervention for all children with early treated Phenylketonuria is recommended.